Whether Today’s Customers are Satisfied?-A Study with Banks - M., Ashok Kumar; R., Rajesh (Indian Journal of Marketing, 2009)
Banks are the mart of the world, the nerve center of economics and are also the barometer of nation’s property. The biggest asset on the balance sheet of banks today is the ignorance of customers of their own rights, and their reluctance to fight for them. Due to globalization and the development of WTO, banking has gone under paradigm shift and has resulted in transformation of whole banking industry. At the same time customer to be satisfied in such a way for the success of the banks performance. This being situation a study has been made on select branches of SBI Associate operating in headquarters of the textile city of coimbatore during the month of May and June. The questions are arranged six various heads such as Infrastructure, Attitudes of the bankers, Services provided, Operations, Attitudes towards ATM and Redresal operations. The study reveals that on an average 80% of its customers are satisfied. Techno-savvy is not up to the mark of the customers which has to be improved. When overall rating has been calculated it can be concluded that State Bank of Travancore stood first as per the study.